KORELASI DENSITAS MAMOGRAFI DAN KADAR ESTRADIOL SERTA PENGARUH BEBERAPA FAKTOR RISIKO KANKER PAYUDARA PADA WANITA SEHAT - , HERINDITA PUSPITANINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : The high prevalence and mortality rate of breast cancer accentuate the importance of prevention and screening on healthy women. Among the risk factors of breast cancer, mammographic density and estradiol level are two main risk factors that suspected to be correlated. Objective : To observe mammographic density and estradiol level in healthy women and their relation to other risk factors, also to observe the correlation between mammographic density and estradiol level on healthy premenopausal and postmenopausal women. Methods : A cross sectional study is done by examining the correlation between follicular estrogen level and mammographic density of 40 screening patients at Klinik Onkologi Kotabaru Yogyakarta, aged between 35-70 years old. Participants are asked to fill a questionaire to obtain information of other risk factors which were believed to have associations with both estradiol and breast density. Mammographic density was analized by thresholding methods and estradiol level was measured with ECLIA. Results : Among several observed risk factors, age and menopausal status were found to be strong negatively correlated with estradiol level (r=-0,612